RECLAMATION OF SPEND MOULDING SANDS WITH THE CARBOPHEN 8178 RESIN (Metallurgy and Foundry Engineering, 2012)
The aim of investigations was to collect the experimental data allowing the quality assessment of the reclaimed material obtained by means of the mechanical reclamation from spent sands with the Carbophen 8178 resin. The investigation program was as follows: •   making the moulding sand with the Carbophen 8178 resin and its preparation for the primary reclamation, •   carrying out the secondary reclamation of the spent sand in the experimental mechanical reclaimer, at several variable parameters (inclination, reclamation time, rotor rotational speed), •   necessary instrumental tests of the reclaimed spent sand and the analysis of the obtained reclaimed materials. Investigations were carried our for three positions of the apparatus: α = 0o, 3o, 6o. The reclamation was performed for each position at three rotational speeds of impact-abrasive elements. The reclamation process effects were checked after 5, 10, 15 and 20 minutes. The reclamation results for the average rotational speed of the rotor, being 700 rpm, are presented in the paper.